Clinicopathological characteristics and prognosis of thyroid cancer in northwest China: A population‐based retrospective study of 2490 patients. Issue 11 (12th September 2018) - Huang, Meiling; Yan, Changjiao; Wei, Hongliang; Lv, Yonggang; Ling, Rui
Abstract : Background: The specific clinical features of thyroid cancer patients in northwest China are unclear; therefore, we analyzed the clinicopathological characteristics and prognosis of this population. Methods: Clinical characteristics including age, gender, blood type, histological type, and BRAF V600E gene mutation; and incidence; risk factors; surgical treatment; and prognosis were recorded. Results: A total of 2490 thyroid cancer patients were included; 98% were diagnosed with papillary thyroid cancer (PTC). Weight, blood type, histological type, and BRAF V600E gene mutation rates were significantly different. Pediatric thyroid cancer patients had higher lymph node metastasis, lower BRAF V600E mutation, and 6.2–9.2% greater recurrence rates than adult patients. PTC and papillary thyroid microcarcinoma displayed similar features, while in other types, such as follicular and medullary thyroid cancer, there were variations. Multiple logistic analyses showed that age (odds ratio [OR] 0.957, 95% confidence interval [CI] 0.944–0.970; P < 0.001), focal status (OR 16.174, 95% CI 9.257–28.262; P < 0.001), pathology (OR 0.642, 95% CI 0.473–0.871; P = 0.004) and lymph node metastasis (OR 0.059, 95% CI 0.033–0.107; P < 0.001) were independent factors for BRAF V600E mutation. Conclusion: Most real world clinicopathological features, treatment, and prognosis of thyroid cancer are similar to reported data, such as the higher incidence of disease in women and the larger proportion of PTC. However, the results in pediatric patients and those with BRAF gene mutations are controversial and require more clinical incidence.